A Life-Cycle Approach to Building Energy Retrofitting: Bio-Based Technologies for Sustainable Urban Regeneration. (June 2019) - Pittau, F; Habert, G; Iannaccone, G
Abstract: The construction sector and, more specifically, the building renovation sector plays a decisive role in the achievement of the EU targets for the reduction of energy consumption and CO2 emissions. The main strategies implemented by the EU are aimed, on one side, at increasing the number of buildings to be renovated and, on the other, at promoting deep renovation on the existing stock. The main objective is to drastically reduce the CO2 emissions associated with the energy consumption of buildings during their operation in consideration of the decarbonization targets by 2050. Several studies have shown that around 75% of the EU building stock needs energy retrofitting, and a significant amount of thermal insulation is expected to be installed on the building envelopes in order to decrease the energy losses. The carbon emission for the production of materials and construction might slow down the transition to a low carbon society and significantly reduce the carbon budget available by 2050. In this perspective, the paper shows the results of some recent research activities aimed at identifying alternative approaches based on the use of biogenic materials applied to the building envelope retrofitting. On one side, they meet the energy and CO2 targets established by the EU while promoting, on the other one, sustainable regeneration processes that include, among the others, the storage of CO2 in building elements and the efficient land use. A specific calculation tool, based on a dynamic LCA method, is introduced to holistically quantify the environmental benefits expected over time.